Emotional Well-Being in Anorexia Nervosa: Negative Affect, Sleeping Problems, Use of Mood-enhancing Drugs and Exercise Frequency - Suzanna Lundblad; Danilo Garcia; Berit Hansson; Trevor Archer (Archives of Depression and Anxiety - Peertechz Publications, 2015)
The purpose of this study was to ascertain emotional well-being among patients presenting ninety anorexia nervosa (AN) and healthy age-matched controls using the Positive Affect and Negative Affect Schedule and the Emotional Well-Being Scale together with background health information. The results indicated that AN patients displayed higher levels of negative affect and negative emotions, more stress and depression, greater sleeping problems, pain, and use of analgesics and mood-enhancing drugs, as well as lower levels of positive affect and positive emotions, compared to the age-matched healthy controls.  Despite  their  negative  self-report,  on  the  variables  pertaining  to  affect,  sleep  and  pain,  the AN patients reported a higher frequency of physical exercise. Regression analysis indicated that the AN  condition,  from  diagnosis,  was  predicted  from  negative  affect,  sleeping  problems,  use  of   mood- enhancing  drugs  and  exercise  frequency.  Hence,  suggesting  that  excessive  exercise  together  with depression, anxiety, obsessive-compulsive, additive behaviors and sleep problems represent AN from a perspective of multiple comorbidities.